СLINICAL AND IMMUNOLOGICAL EFFICIENCY OF IMUNOFAN AND POLYOXIDONIUM IN COMBINED THERAPY OF COMMUNITY-ACQUIRED PNEUMONIA - L. R. Mukhamadieva; G. A. Mavzyutova; R. M. Fazlyeva; N. R. Bikhmetova (Медицинская иммунология)
Abstract. A study was carried out in hundred-five patients with severe or mid-severe clinical courseof community-acquired pneumonia. Clinical observations showed that introduction of Imunofan andPolyoxidonium within combined therapeutic regimen administered to the patients, exerts a pronounced positive effect upon clinical course of disease and normalization of immune characteristics. Due to immunocorrective treatment with Imunofan and Polyoxidonium, the patients with community-acquired pneumonia, exhibited a distinct trend to earlier normalization of both cellular and humoral immunity indexes. This result provides further proofs for efficient treatment with immunomodulatory drugs, e.c., by means of Imunofan and Polyoxidonium.